Kubmalay - Gines, Arthur M. (Animo Repository, 2022)
Kubmalay is a 13-minute fictional psychological horror film that examines the subjects of loneliness, familial trauma, emotional detachment, and isolation. It features Oscar, an estranged member of his family, who begins experiencing paranormal hauntings as he is tormented by an unknown entity, just after reading a letter from his recently deceased father. The film was executed with the intention of providing commentary on corporal parenting exhibited in some Filipino households, as it aims to effectively illustrate the long-term mental and psychological trauma corporal parenting leaves behind on individuals. In addition, the film also aims to serve as an examination of the sentiments of loneliness, isolation, and mental health issues experienced by many during the early onset of the COVID-19 pandemic and quarantine restrictions. That being said, the thematic inspiration for the short feature was mainly taken from the proponents’ friends and their own personal experiences of the pandemic negatively affecting their mental states. With COVID-19 and quarantine regulations in mind, the proponents centered their conceptualization process around a story that was feasible enough to be produced within the confines of proponent 1’s household. The entire material was shot purely at proponent 1’s household during quarantine lockdown. The film does not intend to generalize all aftermaths of corporal parenting, but rather, it aims to provide an opportunity to raise concerns and awareness of the possible long-term detrimental effects corporal parenting can have on individuals in traditional Filipino households.